2015
DOI: 10.1007/978-3-319-21668-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Counterexample-Guided Quantifier Instantiation for Synthesis in SMT

Abstract: Satisfiability Modulo Theories (SMT) solvers have emerged as prominent tools in formal methods applications. While originally targeted towards quantifier-free inputs, SMT solvers are now often used for handling quantified formulas in automated theorem proving and software verification applications. The most common technique for handling quantified formulas in modern SMT solvers in quantifier instantiation. This paper gives an overview of recent advances in quantifier instantiation in SMT. In addition to the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 31 publications
1
131
0
Order By: Relevance
“…In terms of numbers of problems solved there is clear evidence of progress in this important area of ATP, with four of this year's systems solving more problems than CVC4 1.4. In particular, CVC4 1.5 has improved greatly over CVC4 1.4, due to the addition of a new instantiation-based technique [7] that was optimized for quantifiers in pure linear arithmetic, and improved implementations of the various E-matching techniques that are effective on problems combining arithmetic with function symbols. The importance of TFA problems in application domains is growing, and this division will be emphasized in CASC-J8 (the next CASC).…”
Section: The Thf Divisionmentioning
confidence: 99%
“…In terms of numbers of problems solved there is clear evidence of progress in this important area of ATP, with four of this year's systems solving more problems than CVC4 1.4. In particular, CVC4 1.5 has improved greatly over CVC4 1.4, due to the addition of a new instantiation-based technique [7] that was optimized for quantifiers in pure linear arithmetic, and improved implementations of the various E-matching techniques that are effective on problems combining arithmetic with function symbols. The importance of TFA problems in application domains is growing, and this division will be emphasized in CASC-J8 (the next CASC).…”
Section: The Thf Divisionmentioning
confidence: 99%
“…It is often orders of magnitude faster than enumerative syntax-guided techniques, as reported in [23] and corroborated by the 2015 edition of the syntax-guided synthesis competition [2], where its implementation in the SMT solver CVC4 won both the general and conditional linear arithmetic tracks.…”
mentioning
confidence: 70%
“…Previous work [23] has shown that SMT solvers with for support quantifier instantiation already have many of the functionalities required for synthesis. In particular, [23] describes a method to efficiently solve a common class of synthesis conjectures whose properties are single-invocation.…”
Section: First-order Quantifier Instantiation For Single Invocation Pmentioning
confidence: 99%
See 2 more Smart Citations